Kajian Komparasi Penerapan Algoritma C4.5, Neural Network, dan SVM dengan Teknik PSO untuk Pemilihan Karyawan Teladan PT. XYZ - Rudi Apriyadi Raharjo (Universitas Indraprasta PGRI Jakarta, 2017)
Improving the quality of human resources for the company to its employees is needed to be able to increase the growth of the company for the quality of its employees. Systems Information Technology is currently developing very helpful in making accurate decisions. PT. XYZ is a company engaged in the field of Software Developper, very closely with Human Resources issues that continue to rotate to follow the needs of service users, resulting in a less effective employee performance. This study uses a comparative assessment of the C4.5 algorithm, Neural Network and SVM using PSO technique using Rapid Miner software by comparing several classifications. The results of this study is to produce a model that can support decision making in terms of objectively determining the model employee.